Quercus and Pinus cover are determined by landscape structure and dynamics in peri-urban Mediterranean forest patches - Guirado, Maria; Pino, Joan; Rodà, Ferran; Basnou, Corina (Plant Ecology, 2007)
Successional dynamics in Mediterranean forests have been modulated by anthropogenic disturbances during thousands of years, especially in areas densely populated since ancient times. Our objective is to determine whether pine tree cover (early-successional species) and oak tree cover (late-successional species), used as a surrogate of successional stage of peri-urban fragmented forests in the Valle`s lowlands (Catalonia, NE, Spain), are primarily determined by (1) climate and topography; (2) anthropogenic disturbances; (3) patch structure; or (4) patch dynamics from 1956 to 1993. Quercus spp. and Pinus spp. tree cover were separately recorded on 252 randomly selected plots of 100 m 2 , within forest patches ranging in size from 0.25 to 218 ha. Multiple linear regressions indicated that forest patch history is the most important variable determining oak and pine tree cover: new forest patches showed higher pine and lower oak tree cover than recently split patches (i.e. those that became fragmented from large forest areas after 1956). Patches already existing as such in 1956 (pre-existent patches) showed higher pine cover than recently split patches. Oak cover increased and pine cover decreased with increasing forest connectivity of the patch. Finally, highly frequented forests were related to high cover of pines. Climatic and topographic variables were not signiﬁcant. We conclude that pine and oak cover in these peri-urban forests are mainly determined by recent patch dynamics, but also by the spatial pattern of patches. However, humaninduced disturbance can modulate this as there is some evidence for pine being associated with a high human frequentation.
Keywords: á pinus; á quercus forests; anthropogenic disturbances; anthropogenic disturbances á forest; Forest fragmentation; forests á patch structure; fragmentation á historical dynamics; historical dynamics; patch structure; pinus forests; Quercus forests